Szkoła wobec wzrastających oczekiwań prozdrowotnej kompetencji pedeutologii (aktualna rola nauczyciela w dobie medycyny spersonalizowanej) = The School against the increased "Health Promoting" expectations and their Competency of Pedeutology (an active role of a teacher in the period of personalized medicine) - Radziewicz-Winnicki, Andrzej; Radziewicz-Winnicki, Igor (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper consists of several thoughts/proposals toward to the representatives of modern school who take up the responsibility for the development of so called "health promoting - behaviours". They base on the letter written by Polish Commissioner for the Citizen`s Affairs of 18. Jan. 2018, trying to implement among its readers a possibility of serving occasional medical support on the school area, also by teachers for pupils, who need such a health care. Both authors try to discuss on medical problems in the school space and the role of a teacher in the personalized medicine.
Keywords: medycyna spersonalizowana; spersonalizowana opieka zdrowotna; pedeutologia; nowoczesna opieka zdrowotna; aktywność nauczycielska; zachowania prozdrowotne; personalized medicine; personalized health care; pedeutology; modern healthcare; teacher`s activity; health promoting behaviours